Hierarchically structured photoanode with enhanced charge collection and light harvesting abilities for fiber-shaped dye-sensitized solar cells. (July 2018) - Liu, Guicheng; Wang, Manxiang; Wang, Hui; Ardhi, Ryanda Enggar Anugrah; Yu, Hyunjin; Zou, Dechun; Lee, Joong Kee
Abstract: The performances of fiber dye-sensitized solar cells (FDSSCs), in terms of charge collection efficiency, light-harvesting ability, and structural stability, are improved through a novel hierarchically structured photoanode based on a Ti microridge/nanorod-modified wire substrate. The microridge made of several Ti micropits is inserted into TiO2 layer to shorten the photoelectron transport distance from the original place in the TiO2 layer to substrate and to increase the electron transport rate. The Ti micropits are used as light-gathering centers to collect the reflected light. Meanwhile, the Ti nanorods are evenly distributed on the surface of the microridge-coated Ti wire substrate, which increases the contact area between the substrate and the TiO2 layer in order to suppress the electron recombination and scatters the incident light to further improve the light-harvesting ability. Therefore, the charge collection and power conversion efficiencies of the novel FDSSC have been accordingly enhanced by 17.7% and 61.6%, respectively, compared with traditional FDSSC. Moreover, the structural stability of the novel FDSSC has been strengthened. Graphical abstract: The performances such as charge collection efficiency, light-harvesting ability and structural stability of fiber dye-sensitized solar cells (FDSSCs) are improved through a novel hierarchically structured photoanode based on a Ti microridge/nanorod-modified wire-substrate.fx1 Highlights: Hierarchically structured photoanode substrate is a Ti microridge/nanorod-modified wire. Novel design enhances charge collection and light-harvesting abilities, concurrently. Novel FDSSC exhibits the highest PCE of 8.128% in the field of nanocrystalline-based FDSSCs so far. Ti microridges shorten photoelectron transport distance and are used as light-gathering centers. Ti nanorods suppress electron recombination and scatters the incident light.